2016
DOI: 10.1016/j.annepidem.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and trends of leisure-time physical activity by occupation and industry in U.S. workers: the National Health Interview Survey 2004–2014

Abstract: Purpose Studies describing prevalence and trends of physical activity among workers in the United States are scarce. We aimed to estimate prevalence and trends of “sufficient” leisure-time physical activity (LTPA) during the 2004–2014 time period among U.S. workers. Methods Data were collected for U.S. workers in the National Health Interview Survey. LTPA was categorized as sufficiently active (moderate intensity, ≥150 minutes per week), insufficiently active (10–149 minutes per week), and inactive (<10 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…A study from Finland shows an increase in participants engaging in high leisure-time physical activity levels between 1982 and 2012, from 21% to 33% in men and 12% to 27% in women [4]. An increase in leisure-time physical activity level has also been reported in the UK [10], Spain [5], Sweden [7], Canada [8], US [14], and Denmark [9]. In Norway, previous studies of physical activity trends show ambiguous direction and patterns [15][16][17].…”
Section: Introductionmentioning
confidence: 96%
“…A study from Finland shows an increase in participants engaging in high leisure-time physical activity levels between 1982 and 2012, from 21% to 33% in men and 12% to 27% in women [4]. An increase in leisure-time physical activity level has also been reported in the UK [10], Spain [5], Sweden [7], Canada [8], US [14], and Denmark [9]. In Norway, previous studies of physical activity trends show ambiguous direction and patterns [15][16][17].…”
Section: Introductionmentioning
confidence: 96%
“…The other explanation is that police officers spent more time in outdoor physical activities than other occupational groups. Gu et al (2016) reported that the prevalence of sufficient leisure-time physical activity in Protective Service (67% in 2013) was one of the highest among 21 US occupational groups (average 55%). It may be that police officers have more sun exposure than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, this association was observed in older sedentary workers. This finding is somewhat surprising, because previous studies have found sedentary workers to be more physically active during leisure (28) and less fatigued after work compared with physical workers (45, 46). Aging is associated with declines in physical capacity resulting in work tasks potentially being performed at relatively higher physical work demands in older workers compared with their younger counterparts (11).…”
Section: Discussionmentioning
confidence: 73%
“…A study investigating the prevalence and trends of leisure-time physical activity in U.S. workers found that sedentary workers are more physically active during leisure compared with physical workers (28). Moreover, previous studies have reported a decline in physical activity with age (8, 11, 1921).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation